Identification and sequence analysis of Escherichia coli purE and purK genes encoding 5'-phosphoribosyl-5-amino-4-imidazole carboxylase for de novo purine biosynthesis. - Watanabe, W (1989)
It has been shown that the Escherichia coli purE locus specifying 5'-phosphoribosyl-5-amino-4-imidazole carboxylase in de novo purine nucleotide synthesis is divided into two cistrons. We cloned and determined a 2,449-nucleotide sequence including the purE locus. This sequence contains two overlapped open reading frames, ORF-18 and ORF-39, encoding proteins with molecular weights of 18,000 and 39,000, respectively. The purE mutations of CSH57A and DCSP22 were complemented by plasmids carrying ORF-18, while that of NK6051 was complemented by plasmids carrying ORF-39. Thus, the purE locus consists of two distinct genes, designated purE and purK for ORF-18 and ORF-39, respectively. These genes constitute a single operon. A highly conserved 16-nucleotide sequence, termed the PUR box, was found in the upstream region of purE by comparing the sequences of the purF and purMN operons. We also found three entire and one partial repetitive extragenic palindromic (REP) sequences in the downstream region of purK. Roles of the PUR box and REP sequences are discussed in relation to the genesis of the purEK operon.